Esterification of acetic acid with alcohol isoamyl in the presence of enzymatic catalyst - Nádia Ligianara Nyari; Alessandro Rogerio Paulazzi; Raquel Vera Zamadei; Jamile Zeni; Rogério Marcos Dallago (Evidência, 2019)
The Candida antarctica Lipase B immobilized on polyurethane catalysed esterification of acetic acid with isoamyl alcohol in mechanical and ultrasonic system in a system solvent-free, was studied. The maximum esterification of isoamyl acetate used immobilized catalyst was the highest esterification, 666.05 U/g with 19 cycles of reuse after 360 minutes of reaction time in mechanical system and 1319.48 U/g was observed and 14 cycles de reuse after 60 minutes of reaction time in ultrasound system. Thus, the process was considered efficient with significant reduction of the reaction time, low instrumental requirements and improve the bioprocess performance. Until now, there were no studies available in the open literature in relation to the ester synthesis catalyzed by immobilized Lipase in polyurethane as support in the ultrasound system. In addition, considered an environmentally correct and economically viable technology, it can be used in cosmetics, pharmaceuticals and food industry.